2011
DOI: 10.3852/10-382
|View full text |Cite
|
Sign up to set email alerts
|

A new annulate Pluteus variety from Italy

Abstract: Pluteus aurantiorugosus, var. aurantiovelatus var. nov., is described from Italy based on both morphological and ITS rDNA data. This taxon is characterized by an ornamented stipe provided with reddish orange remnants of a partial veil. The occurrence of the partial veil in Pluteus also is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The genus is found primarily in association with well-rotted wood and it is characterized by free lamellae, absence of a volva, pinkish spore print, inamyloid basidiospores and inverse hymenophoral trama (Singer 1986). Recent molecular and morphological studies (Minnis et al 2006;Corriol & Moreau 2007;Menolli et al 2010;Vizzini & Ercole 2011;Justo et al 2011a, b) found Pluteus to include some annulate species previously placed in the genus Chaemaeota (W.G. Sm.)…”
Section: Introductionmentioning
confidence: 99%
“…The genus is found primarily in association with well-rotted wood and it is characterized by free lamellae, absence of a volva, pinkish spore print, inamyloid basidiospores and inverse hymenophoral trama (Singer 1986). Recent molecular and morphological studies (Minnis et al 2006;Corriol & Moreau 2007;Menolli et al 2010;Vizzini & Ercole 2011;Justo et al 2011a, b) found Pluteus to include some annulate species previously placed in the genus Chaemaeota (W.G. Sm.)…”
Section: Introductionmentioning
confidence: 99%
“… aurantiovelatus , P. fenzlii , and P. mammillatus suggests that the occurrence or nonoccurrence/ lack of the partial veil in the evolutionary history of Pluteus occurred independently. As stated by Singer states ( Singer 1958 ; Minnis and Sundberg 2010 ; Justo et al 2011a , 2011b ; Vizzini and Ercole 2011 ), this characteristic is homoplasic and unsuitable for the natural classification of these fungi at the supraspecific rank.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies ( Minnis et al 2006 ; Menolli et al 2010; Justo et al 2011a , 2011b ; Vizzini and Ercole 2011 ) have indicated that sect. Celluloderma includes species characterized by the presence of non-metuloid pleurocystidia and a pileipellis that is either euhymeniderm or epithelioid hymeniderm, composed of short elements, which may or may not be intermixed or not with elongate cystidioid elements (corresponding to Pluteus sect.…”
Section: Introductionmentioning
confidence: 99%
“…Universal primers ITS1F/ITS4 were used for the ITS region amplification (White et al 1990, Gardes & Bruns 1993). Amplification reactions were performed in a PE9700 thermal cycler (Perkin-Elmer, Applied Biosystems) following Vizzini et al (2011). The PCR products were purified with the AMPure XP kit (Beckman) and sequenced by MACROGEN (Seoul, Republic of Korea).…”
Section: Methodsmentioning
confidence: 99%